Tanggung Jawab Kurator Dalam Perkara Kepailitan Berdasarkan Prinsip Independensi - Sunaryo Sunaryo; Dina Haryati Sukardi (Universitas Sang Bumi Ruwa Jurai, 2023)
The curator must be independent and not have a conflict of interest because the curator has such great authority over bankruptcy assets. The research used in this research is normative legal research. This is because researchers use library materials as data to analyze cases in the preparation of this study. provisions regarding the principle of independence are emphasized in the Code of Ethics of the Indonesian Curator and Administrator Association (AKPI) which states that in every appointment received, members of the Indonesian Curator and Administrator Association (hereinafter referred to as